Meta-Analysis the Effect of Aquatic Therapy on Functional Ability in Patients with Knee Osteoarthritis - Puspita, Wita Hana; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Knee OA can affect mobility in the elderly causing pain and impaired functional ability. This study aims to analyze the effect of aquatic therapy on functional ability in knee osteoarthritis patients based on the results of a number of previous primary studies..Subject and Method: This study was conducted using a meta-analysis method with articles searched using the search keywords